2016
DOI: 10.1089/neu.2015.4173
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Microthrombi in Parenchymal Microvessels after Traumatic Brain Injury Is Independent of Coagulation Factor XI

Abstract: Microthrombus formation and bleeding worsen the outcome after traumatic brain injury (TBI). The aim of the current study was to characterize these processes in the brain parenchyma after experimental TBI and to determine the involvement of coagulation factor XI (FXI). C57BL/6 mice (n = 101) and FXI-deficient mice (n = 15) were subjected to controlled cortical impact (CCI). Wild-type mice received an inhibitory antibody against FXI (14E11) or control immunoglobulin G 24 h before or 30 or 120 min after CCI. Cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Injury-induced decreases in CBF and microvascular circulation can result in microthrombus formation (Schwarzmaier et al, 2016) and tissue hypoxia (Bragin et al, 2016). Compared with sham animals, animals exposed to CCI had a greater incidence of stationary leukocyte-platelet aggregates in parenchymal capillaries (Schwarzmaier et al, 2016). Microthrombus aggregation can lead to secondary injuries, including hematoma formation and edema.…”
Section: Evidence From Human Patientsmentioning
confidence: 99%
“…Injury-induced decreases in CBF and microvascular circulation can result in microthrombus formation (Schwarzmaier et al, 2016) and tissue hypoxia (Bragin et al, 2016). Compared with sham animals, animals exposed to CCI had a greater incidence of stationary leukocyte-platelet aggregates in parenchymal capillaries (Schwarzmaier et al, 2016). Microthrombus aggregation can lead to secondary injuries, including hematoma formation and edema.…”
Section: Evidence From Human Patientsmentioning
confidence: 99%
“…Interestingly, in a study evaluating traumatic brain injury in FXI‐deficient mice, cerebral thrombogenesis was not reduced by FXI deficiency 29 . The same study also reported that reduced FXI levels were not associated with increased risk of ICH in mice 29 …”
Section: Discussionmentioning
confidence: 93%
“…Regarding the patient whose head injury was complicated by cranial sinus vein thrombosis, it is an increasingly reported complication of traumatic head injury 28 . Interestingly, in a study evaluating traumatic brain injury in FXI‐deficient mice, cerebral thrombogenesis was not reduced by FXI deficiency 29 . The same study also reported that reduced FXI levels were not associated with increased risk of ICH in mice 29 …”
Section: Discussionmentioning
confidence: 99%
“…By using two-photon microscopy, tissue oxygenation, the diameters of single arterioles and capillaries at different depths in the brain cortex are measured (Tiana et al, 2010;Devor et al, 2011;Kasischke et al, 2011;Schwarzmaier et al, 2016). As for calcium flux, the astrocytes play a key role, when oxygen is limited after BBB breakdown, the astrocyte glycolysis and lactate release are maximized.…”
Section: Cerebral Metabolism Imbalancementioning
confidence: 99%